First report of partial albinism in genus Thrichomys (Rodentia: Echimyidae) - Antonio Carlos da S.A. Neves; Ludmilla Carvalho Coutinho; Marcione B. de Oliveira; Leila Maria Pessôa (Papéis Avulsos de Zoologia, 2014)
Reports about albinism in rodents are common. In the family Echimyidae, however, albinism is very rare. This is the second case of coat color variation reported within Echimyidae and the first for the genus Thrichomys. The pelages of Thrichomys pachyurus individuals with normal and variant coat color were observed under a fluorescent artificial light and were examined with a stereoscopic microscope. The descriptions of pelage color were based on the book "Color Standards and Color Nomenclature". The predominantly white pattern of coat color in individuals of T. pachyurus suggests a partial albinism caused by delay in migration time of melanoblasts from neural crest to epidermis. The habitat of T. pachyurus has a heavy vegetative cover, which offers natural protection against predators and high-quality nutrition.